2015
DOI: 10.1158/1078-0432.ccr-14-2082
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab in Patients with Nonsquamous Non–Small Cell Lung Cancer and Asymptomatic, Untreated Brain Metastases (BRAIN): A Nonrandomized, Phase II Study

Abstract: Purpose: The phase II prospective, noncomparative BRAIN study (NCT00800202) investigated efficacy and safety of bevacizumab in chemotherapy-na€ ve or pretreated patients with nonsmall cell lung cancer (NSCLC) and asymptomatic untreated brain metastases to provide data in this previously unexplored subgroup.Experimental Design: Patients with stage IV nonsquamous NSCLC, Eastern Cooperative Oncology Group performance status 0-1, and untreated, asymptomatic brain metastases received first-line bevacizumab (15 mg/k… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
120
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(132 citation statements)
references
References 30 publications
5
120
0
5
Order By: Relevance
“…82 Some efficacy with acceptable safety has been suggested in a phase II study of patients with asymptomatic untreated brain metastases from NSCLC with bevacizumab in combination with paclitaxel and carboplatin (class IIb). 83 A recent early analysis of a phase II trial of the programmed cell death protein 1 inhibitor pembrolizumab has shown activity in untreated or previously irradiated brain metastases from NSCLC, 84 but the trial is still ongoing.…”
Section: Brain Metastases From Nsclcmentioning
confidence: 99%
“…82 Some efficacy with acceptable safety has been suggested in a phase II study of patients with asymptomatic untreated brain metastases from NSCLC with bevacizumab in combination with paclitaxel and carboplatin (class IIb). 83 A recent early analysis of a phase II trial of the programmed cell death protein 1 inhibitor pembrolizumab has shown activity in untreated or previously irradiated brain metastases from NSCLC, 84 but the trial is still ongoing.…”
Section: Brain Metastases From Nsclcmentioning
confidence: 99%
“…Intracranial responses with cytotoxic chemotherapy usually correlate with systemic responses in patients with NSCLC. Intracranial response rates as high as 68% have been reported with chemotherapy in asymptomatic patients 81 ; however, PFS is usually limited to several months, and OS ranges from 5 to 16 months (Table 4). The best intracranial outcomes were achieved using regimens containing cisplatin and pemetrexed 82,83 or bevacizumab, carboplatin, and paclitaxel.…”
Section: Chemotherapymentioning
confidence: 99%
“…An increasing body of evidence indicates that the use of bevacizumabbased therapy seems to be feasible and safe in patients with CNS metastases from NSCLC (33). Moreover first-line bevacizumab in combination to standard chemotherapy demonstrated promising activity in patient with asymptomatic BM from NSCLC in the BRAIN trial (36). Even if treated CNS metastases were allowed in phase II (47,48) and III (46) with ramucirumab, no data are actually available about the efficacy of ramucirumab in this subgroup of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Besse et al conducted a non-randomized, phase II trial to investigate bevacizumab-based regimens in both first and second line setting in patients with NSCLC and asymptomatic, untreated BM (BRAIN trial) (36). Sixtyseven patients were treated with first line bevacizumab in combination with carboplatin and paclitaxel and 24 patients received second line bevacizumab in combination with erlotinib.…”
Section: Angiogenesis In Brain Metastasesmentioning
confidence: 99%